Analisis Hukum Pidana Islam terhadap Orang yang Membantu Aborsi - Faisol, Faisol; Malik, Arif Jamaludin (Al-Jinayah : Jurnal Hukum Pidana Islam, 2020)
Abortion as a crime has a long story and many people do not realize that abortion is related to the public wellbeing issue. Within the Islamic's perspective, fetus removal is prohibited because it kills the fetus (human candidate) which is glorified by Allah SWT. Ironically, abortion is supported by some groups. The impact is that there are an estimated 2,000,000 cases of abortion that occur each year in Indonesia. This paper concludes that the punishment received by the perpetrators who are indirect actors comes below the term of ta'zir offense. Where the form, the amount, and the way of its sentence being carried out are under the judge's discretion. It is demanded that the authorities should be bolder and more resolute in punishing offenders so that the harsher the punishment is given, the more likely it would deter. The public is demanded to be cautious against any persuasion efforts, incitement, and other forms of influencing that made them a party in a crime.